1976
DOI: 10.1007/bf01071903
|View full text |Cite
|
Sign up to set email alerts
|

The use ofd-limonene preparation as a dissolving agent of gallstones

Abstract: The dissolving mixture is administered through a choledochal drain to treat postoperatively retained cholesterol gallstones. It is prepared by mixing 97.0 parts of d-limonene with 2.1 parts of polysorbate 80 and 0.9 part of sorbitan monooleate, a mixture of which may easily reach the surface of the gallstones which are wetted by bile. The d-limonene preparation was found to be safe both in laboratory experiments and clinical trials. Before applying the preparation, the usual choledochal drain must be replaced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

1979
1979
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(14 citation statements)
references
References 11 publications
0
13
0
1
Order By: Relevance
“…Since this preparation seemed, therefore, to be substantially free from side-effects, we felt that any claims of efficacy deserved careful consideration. Several of the terpenes in Rowacholfor example, menthol, menthone, pinene-have long been shown to be excellent cholesterol solvents in vitro, and indeed the structurally related terpene, d-limonene, has recently been advocated as an agent for dissolving retained common duct stones (Igimi et al, 1976). However, it is unlikely that significant amounts of these compounds appear in bile because of their relatively low molecular weight (Smith, Biliary bile acid concentration was measured enzymatically using 3ohydroxysteroid dehydrogenase (Talalay, 1960).…”
mentioning
confidence: 99%
“…Since this preparation seemed, therefore, to be substantially free from side-effects, we felt that any claims of efficacy deserved careful consideration. Several of the terpenes in Rowacholfor example, menthol, menthone, pinene-have long been shown to be excellent cholesterol solvents in vitro, and indeed the structurally related terpene, d-limonene, has recently been advocated as an agent for dissolving retained common duct stones (Igimi et al, 1976). However, it is unlikely that significant amounts of these compounds appear in bile because of their relatively low molecular weight (Smith, Biliary bile acid concentration was measured enzymatically using 3ohydroxysteroid dehydrogenase (Talalay, 1960).…”
mentioning
confidence: 99%
“…D-Limonene is listed as generally recognized as safe in the Code of Federal Regulation (USA) for a flavouring agent. It is considered as an excellent solvent for cholesterol and is used clinically to dissolve cholesterol in gall stones (Igimi et al, 1976). Limonene is clinically proven to be effective in the treatment of chronic heartburn or gastro-oesophageal reflux disorder (Wilkins, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Other agents that have been infused include lecithin (116), quaternary amines (111), and the terpene d-limonene (120). We found that the infusion of monoglyceride solutions caused diarrhea.…”
Section: Heparin Infusionmentioning
confidence: 94%